Orally bioavailable RORγ/DHODH dual host-targeting small molecules with broad-spectrum antiviral activity - Herrmann, Alexandra; Gege, Christian; Wangen, Christina; Wagner, Sabrina; Kögler, Melanie; Cordsmeier, Arne; Irrgang, Pascal; Ip, Wing Hang; Weil, Tatjana; Hunszinger, Victoria; Groß, Rüdiger; Heinen, Natalie; et al. (Antiviral Research, 2024)
Host-directed antivirals (HDAs) represent an attractive treatment option and a strategy for pandemic preparedness, especially due to their potential broad-spectrum antiviral activity and high barrier to resistance development. Particularly, dual-targeting HDAs offer a promising approach for antiviral therapy by simultaneously disrupting multiple pathways essential for viral replication. Izumerogant (IMU-935) targets two host proteins, (i) the retinoic acid receptor-related orphan receptor γ isoform 1 (RORγ1), which modulates cellular cholesterol metabolism, and (ii) the enzyme dihydroorotate dehydrogenase (DHODH), which is involved in de novo pyrimidine synthesis. Here, we synthesized optimized derivatives of izumerogant and characterized their antiviral activity in comparison to a recently described structurally distinct RORγ/DHODH dual inhibitor. Cell culture-based infection models for enveloped and non-enveloped DNA and RNA viruses, as well as a retrovirus, demonstrated high potency and broad-spectrum activity against human viral pathogens for RORγ/DHODH dual inhibitors at nanomolar concentrations. Comparative analyses with equipotent single-target inhibitors in metabolite supplementation approaches revealed that the dual-targeting mode represents the mechanistic basis for the potent antiviral activity. For SARS-CoV-2, an optimized dual inhibitor completely blocked viral replication in human airway epithelial cells at 5 nM and displayed a synergistic drug interaction with the nucleoside analog molnupiravir. In a SARS-CoV-2 mouse model, treatment with a dual inhibitor alone, or in combination with molnupiravir, reduced the viral load by 7- and 58-fold, respectively. Considering the clinical safety, oral bioavailability, and tolerability of izumerogant in a recent Phase I study, izumerogant-like drugs represent potent dual-targeting antiviral HDAs with pronounced broad-spectrum activity for further clinical development.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Broad-spectrum antiviral; DHODH inhibitor; Dual-targeting small molecules; Host-targeting antiviral; Human viruses; RORγ inhibitor